1H and 13C NMR Spectral Data of Neolignans Isolated from Piper Species - do Nascimento Marinho, Rosiane F.; Angrisani, Bianca R. P.; Macedo, Arthur Ladeira; de Lima Moreira, Davyson; Ribeiro, Carlos Magno Rocha; Vasconcelos, Thatyana Rocha Alves; Valverde, Alessandra Leda (Current Organic Chemistry, 2020)
Plants of the genus Piper (Piperaceae) have a pantropical distribution. In Brazil, Piper species are used in traditional medicine to treat many diseases such as inflammation, diabetes, toothache, and fever. Many reports have shown a correlation between the biological activities of Piper species and neolignans, a secondary metabolite class obtained from the shikimic acid biosynthetic pathway. This review aims to provide detailed information on the structural identification of neolignans isolated from Piper species by 1H and 13C Nuclear Magnetic Resonance (NMR) spectroscopy. These searchable data enable rapid identification and routine analysis of neolignans from extracts of the Piper species.
Keywords: Piperaceae